Epigenetic modifications in breast cancer: from immune escape mechanisms to therapeutic target discovery - Kang, Ziyu; Wang, Junlin; Liu, Jiyan; Du, Li; Liu, Xiaofei (Frontiers in Immunology, 2025)
Breast cancer (BC) is one of the most prevalent malignant tumors among women globally, with the number of cases accounting for even more than 1/3 of all tumor patients in women. Recent studies have found that the incidence of BC is increasing every year. Despite the great progress made in BC treatment, the characteristics of BC cells, such as strong immune evasion, easy recurrence and drug resistance, are still the main reasons limiting the survival of BC patients. Epigenetics is becoming an important method to reveal the development of cancer, mainly through the study of DNA methylation, histone modification, chromatin structure changes and non-coding RNA. In addition, researchers have found that epigenetic markers have great potential for early detection and personalized treatment of BC. Inhibitors targeting epigenetically modified enzymes are effective in treating a wide range of tumors and provide significant patient survival and quality of life. Therefore, this review will comprehensively summarize the role of epigenetic modifications in BC development. Second, this paper will focus on summarizing how epigenetic modifications induce the formation of tumor immune microenvironment (TIME) in BC. Targeting the mechanism of action of epigenetic modifications provides new perspectives to unravel the complex process of BC development, while paving the way for the development of novel diagnostic and therapeutic targets. In the future, by integrating multi-omics data to enable a deeper understanding of the pathogenesis of BC, we will be able to promote the overall development of precision medicine.